A new pathway: how can funders support meaningful monitoring, evaluation, and learning practice in the field? - and Acevedo, Andrea; Colnar, Megan (2023)
How can donors and grantees work together to create effective monitoring, evaluation, and learning (MEL) practices that drive field-wide transformation?